PENGOLAHAN LIMBAH CAIR INDUSTRI RUMAH TANGGA DENGAN ADSORPSI DAN PRETREATMENT NETRALISASI DAN KOAGULASI DI SUNGAI PEMATANG SIANTAR - Sinaga, Mardame Pangihutan; Simanullang, Ady Frenly (Program Studi Teknologi Hasil Perikanan|Fakultas Pertanian|Universitas PGRI Banyuwangi, 2022)
The household industrial liquid waste does not meet the quality standards of the Minister of Environment Regulation Number 5 0f 2014, so it needs to be processed so that it does not pollute the environment. This study aims to examine the effect of the dose of Poly Alum Chloride (PAC) coagulant on the reduction of Pb, Cr, and TDS, examine the quality of wastewater after being neutralized, coagulated, and adsorbed, especially for parameters Pb, Cr, TDS, and pH. The variables in this study were PAC doses, namely 150 mg/l, 200 mg/l, and 250 mg/l. the research was conducted on a laboratory scale with a continuous system with a downflow. The adsorption media used were palm fiber, coconut fiber, bagasse-activated carbon, and zeolite which were arranged in stages in a PVC pipe reactor. The entry of Pb, Cr, and TDS into the human body can be through foods from plants that are commonly consumed by humans such as rice, tea, and vegetables. Pb metal enters the waters through the crystallization of Pb, Cr, and TDS in the air with the help of rain. In addition, the certification process of mineral rocks is also one of the entry routes for Pb, Cr, and TDS sources into the waters. Researchers are interested in researching the processing of household industrial wastewater so that it can be used by the surrounding residents.